EFFECTS OF BLAINVILLEA ACMELLA ON THE BONE MECHANICAL PROPERTIES OF OVARIECTOMIZED RATS (Jurnal Teknologi (Sciences & Engineering), 2025)
A metabolic bone disorder known as osteoporosis is represented by low mineral bone mass and strength. Blainvillea acmella (BA), a herbal plant with antioxidant properties have exhibited anti-osteoporosis effects. The present study set out to discover the osteoprotective effects of BA on bone mechanical properties of the ovariectomized rat model of osteoporosis. Twenty-four Sprague-Dawley female rats were designated into four groups (n=6 per group), namely, (SHAM) sham-operated, (OVX) ovariectomized control, (OVX+E) ovariectomized and supplemented with Premarin 64.5 µg/kg and (OVX+BA) ovariectomized and supplemented with 100 mg/kg of BA ethanolic leaves extract. All rats were euthanized after 12 weeks and the right femurs were tested in three-point bending using Instron Universal Test Machine (Shimadzu AG-X 500N). The bone mechanical properties were evaluated in two parts: extrinsic factors (load, displacement and stiffness) as well as intrinsic factors (stress, strain and Young modulus). The maximum stress and Young modulus of OVX+E and OVX+BA groups indicated considerably higher levels compared to SHAM and OVX groups (p<0.05). No significant differences were found in bone strength between OVX+E and OVX+BA groups. In conclusion, BA leaves extract was comparable to Premarin in maintaining optimal bone strength of the ovariectomized rat model of osteoporosis. Therefore, BA potential in treatment of osteoporosis warrants further investigation.